Molecular Engineering of Conjugated Acetylenic Polymers for Efficient Cocatalyst-free Photoelectrochemical Water Reduction - Sun, Hanjun; Oener, Ibrahim Halil; Wang, Tao; Zhang, Tao; Selyshchev, Oleksandr; Neumann, Christof; Fu, Yubin; Liao, Zhongquan; Xu, Shunqi; Hou, Yang; Turchanin, Andrey; Zahn, Dietrich R. T.; et al. (Angewandte Chemie International Edition, 2019)
Conjugated polymers featuring tunable band gaps/positions and tailored active centers, are attractive photoelectrode materials for water splitting. However, their exploration falls far behind their inorganic counterparts. Herein, we demonstrate a molecular engineering strategy for the tailoring aromatic units of conjugated acetylenic polymers from benzene- to thiophene-based. The polarized thiophene-based monomers of conjugated acetylenic polymers can largely extend the light absorption and promote charge separation/transport. The C≡C bonds are activated for catalyzing water reduction. Using on-surface Glaser polycondensation, as-fabricated poly(2,5-diethynylthieno[3,2-b]thiophene) on commercial Cu foam exhibits a record H2-evolution photocurrent density of 370 μA cm−2 at 0.3 V vs. reversible hydrogen electrode among current cocatalyst-free organic photocathodes (1–100 μA cm−2). This approach to modulate the optical, charge transfer, and catalytic properties of conjugated polymers paves a critical way toward high-activity organic photoelectrodes.
CRIS-Team Scopus Importer:2022-04-14
Keywords: cocatalyst-free photocathodes; conjugated polymers; Glaser polycondensation; hydrogen evolution; molecular engineering